Ответ:
Пошаговое объяснение:Приводим к общему знаменателю
305. 5х+45-3х=15
2х-15-45
Х=-30/2
Х=-15
306. 3х-18-4х=12
-х=12+18
Х= -30
307. 4х+х=45
5х=45
Х=9
308. 2х+х=12
3х=12
Х=4
309. 2х-5х= -30
-3х=-30
Х=10
310. 3х-4х=-12
-х=-12
Х=12
311. 2х-8+3х=30
5х=38
Х=38:5
Х=7,6
312. 2х+3х-3=24
5х=27
Х=5,4
313. 3х-3=8+4х
-х=11
Х=-11
314. 9х-6=10+5х
4х=16
315. Х-4-8=2х
-х=12
Х= -12
316. 6х+42+6=2х
4х=-48
Х=-12
317. 5х+45-3х+3=30
2х=30-45-3
2х=-18
Х=-9
318. 5х-20-2х+2=30
5х-2х=30+20-2
3х=48
Х=48:3
Х=16
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:Приводим к общему знаменателю
305. 5х+45-3х=15
2х-15-45
Х=-30/2
Х=-15
306. 3х-18-4х=12
-х=12+18
Х= -30
307. 4х+х=45
5х=45
Х=9
308. 2х+х=12
3х=12
Х=4
309. 2х-5х= -30
-3х=-30
Х=10
310. 3х-4х=-12
-х=-12
Х=12
311. 2х-8+3х=30
5х=38
Х=38:5
Х=7,6
312. 2х+3х-3=24
5х=27
Х=5,4
313. 3х-3=8+4х
-х=11
Х=-11
314. 9х-6=10+5х
4х=16
Х=4
315. Х-4-8=2х
-х=12
Х= -12
316. 6х+42+6=2х
4х=-48
Х=-12
317. 5х+45-3х+3=30
2х=30-45-3
2х=-18
Х=-9
318. 5х-20-2х+2=30
5х-2х=30+20-2
3х=48
Х=48:3
Х=16